Multidisciplinary Kaizen Event to Improve Adherence to a Sepsis Clinical Care Guideline. Issue 4 (July 2021) - Denicolo, Kimberly S.; Corboy, Jacqueline B.; Simon, Norma-Jean E.; Balsley, Kate J.; Skarzynski, Daniel J.; Roben, Emily C.; Alpern, Elizabeth R.
Abstract : Introduction: Since 2015, the Ann and Robert H. Lurie Children's Hospital Emergency Department (ED) has improved the recognition and treatment of pediatric sepsis and septic shock. Despite existing clinical care guidelines, the ED had not yet achieved the Surviving Sepsis Campaign timeliness goals for fluid and antibiotic administration. Methods: The team conducted a multidisciplinary Kaizen event to evaluate clinical workflows and identify opportunities to improve sepsis care adherence. Using rigorous quality improvement methodology, frontline providers mapped workflows to identify barriers and prioritize emerging solutions. Results: Thirty-seven staff members across 17 disciplines participated. Nurses and physicians identified communication gaps at pathway initiation. Access to supplies, inadequate task delegation, and a lack of urgency for a subset of pathway patients delayed treatment. Prioritized interventions included scripted communication tools, a delineated response plan, and standardized reassessment processes. Revisions to the key driver diagram were made after the improvement event, guiding future plan-do-study-act cycles. Conclusions: Frontline provider participation in the Kaizen event uncovered barriers to care and identified the root causes of ineffective communication and system process inefficiencies. Engaging key stakeholders from multiple care areas in a candid context was a novel approach to process improvement within our department. The Kaizen methodology is fundamental to developing sustainable quality improvement practices, creating momentum for a continuous improvement culture to engrain quality improvement in practice. The success of Kaizen will shape the format of future ED improvement projects. Abstract : Supplemental Digital Content is available in the text.